DISTRIBUTIVITY AND SYMMETRY IN SPATIAL CONFIGURATION OF RURAL HOMES. EL KANTARA (BISKRA) CASE STUDY - ACHERARD, Sabrina; HAMOUDA, Abida; BENYAHIA, Lamia; ASSASSI, Abdelhalim (International Journal of Innovative Technologies in Social Science, 2023)
Several studies have addressed the mode of evolution of inhabited space and several methproposed to understand the interface between user and space and its impact on spatial configuration. In this field, space syntax provides a theory and a method for analyzing the correlation between spatial properties and the behavior of people in inhabited space and the modeling of space according to endogenous and exogenous influences. El Kantara, a case study, was predominant in pre-colonial and colonial times by the traditional vernacular type of architecture. After independence, the so-called modern construction took over. The objective is to shed light on constants and evolutions by a diachronic reading through the use of the spatial syntax method which is a set of techniques for the representation, quantification and interpretation of the spatial configuration of the built environment. Each house was analyzedaccording to its distributivity/non-distributivity corroborated by control visibility and symmetry/asymmetry corroborated by integration visibility recommended by space syntax and elaborated by depthmap. The results show that the genotype of El Kantara dwelling has undergone changes throughout its journey from the nineteenth century to the present day. The mainly constant is that it has always been a question of establishing a demarcation between the inner sphere and the outer sphere and that the spatial configuration takes many forms and revealed degrees ofrupture with respect to the outside.